EASY WADIAH SAVINGS ANALYSIS OF CUSTOMER INTEREST AT BANK SYARIAH INDONESIA - Tasya Maharani; Nisrina Aulia; Siti Julaeha; Andi Amri (PT. Arsil Reka Engineering, 2024)
Bank Syariah Indonesia (BSI) is a financial institution that offers a variety of products, including savings with wadiah contracts (maintaining the authenticity of assets) known as